Crosstalks between Raf-kinase inhibitor protein and cancer stem cell transcription factors (Oct4, KLF4, Sox2, Nanog) - SoHyun Lee; Stephanie Wottrich; Benjamin Bonavida (Tumor Biology)
Raf-kinase inhibitor protein has been reported to inhibit both the Raf/mitogen extracellular signal–regulated kinase/extracellular signal–regulated kinase and nuclear factor kappa-light-chain of activated B cells pathways. It has also been reported in cancers that Raf-kinase inhibitor protein behaves as a metastatic suppressor as well as a chemo-immunosensitizing factor to drug/immune-mediated apoptosis. The majority of cancers exhibit low or no levels of Raf-kinase inhibitor protein. Hence, the activities of Raf-kinase inhibitor protein contrast, in part, to those mediated by several cancer stem cell transcription factors for their roles in resistance and metastasis. In this review, the existence of crosstalks in the signaling pathways between Raf-kinase inhibitor protein and several cancer stem cell transcription factors (Oct4, KLF4, Sox2 and Nanog) was assembled. Oct4 is induced by Lin28, and Raf-kinase inhibitor protein inhibits the microRNA binding protein Lin28. The expression of Raf-kinase inhibitor protein inversely correlates with the expression of Oct4. KLF4 does not interact directly with Raf-kinase inhibitor protein, but rather interacts indirectly via Raf-kinase inhibitor protein’s regulation of the Oct4/Sox2/KLF4 complex through the mitogen-activated protein kinase pathway. The mechanism by which Raf-kinase inhibitor protein inhibits Sox2 is via the inhibition of the mitogen-activated protein kinase pathway by Raf-kinase inhibitor protein. Thus, Raf-kinase inhibitor protein’s relationship with Sox2 is via its regulation of Oct4. Inhibition of extracellular signal–regulated kinase by Raf-kinase inhibitor protein results in the upregulation of Nanog. The inhibition of Oct4 by Raf-kinase inhibitor protein results in the failure of the heterodimer formation of Oct4 and Sox2 that is necessary to bind to the Nanog promoter for the transcription of Nanog. The findings revealed that there exists a direct correlation between the expression of Raf-kinase inhibitor protein and the expression of each of the above transcription factors. Based on these analyses, we suggest that the expression level of Raf-kinase inhibitor protein may be involved in the regulation of the cancer stem cell phenotype.